2006
DOI: 10.1111/j.1601-183x.2006.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Association evidence of schizophrenia with distal genomic region of NOTCH4 in Taiwanese families

Abstract: Evidence for association with schizophrenia has been reported for NOTCH4, although results have been inconsistent. Previous studies have focused on polymorphisms in the 5 0 promoter region and first exon of NOTCH4. Our aim was to test the association of the entire genomic region of NOTCH4 in 218 families with at least two siblings affected by schizophrenia in Taiwan. We genotyped seven single nucleotide polymorphisms (SNPs) of this gene, with average intermarker distances of 5.3 kb. Intermarker linkage disequi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The lack of strength in association called for additional large family‐based studies utilizing haplotype‐tagging SNPs to identify NOTCH4 genetic risk variants. After this meta‐analysis we conducted an independent family‐based association study with 218 nuclear families multiply affected with schizophrenia recruited from hospitals across Taiwan [Liu et al, 2007]. This analysis adopted the systematic approach of utilizing haplotype‐tagging SNPs to test for association in this large family sample, as the prior work had suggested.…”
Section: Initial Identification Of Notch4 As a Schizophrenia Candidatmentioning
confidence: 99%
“…The lack of strength in association called for additional large family‐based studies utilizing haplotype‐tagging SNPs to identify NOTCH4 genetic risk variants. After this meta‐analysis we conducted an independent family‐based association study with 218 nuclear families multiply affected with schizophrenia recruited from hospitals across Taiwan [Liu et al, 2007]. This analysis adopted the systematic approach of utilizing haplotype‐tagging SNPs to test for association in this large family sample, as the prior work had suggested.…”
Section: Initial Identification Of Notch4 As a Schizophrenia Candidatmentioning
confidence: 99%
“…Furthermore, rs2071287 and rs3131296, which display very strong LD with each other, were identified as the SNPs that are most likely to be functionally relevant to SCZ etiology, suggesting that it is necessary to determine the association of rs2071287 with SCZ [ 12 , 13 ]. Another SNP, rs204993, was found to be significantly associated with SCZ through a family-based association study of 218 Taiwan nuclear families [ 14 ]. To date, few studies have investigated the association of NOTCH4 with SCZ in the Chinese population, particularly regarding the SNPs rs2071287 and rs204993.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies also confirmed the relationship between schizophrenia and NOTCH4 polymorphisms, including microsatellite (Glatt et al, 2005) and single nucleotide polymorphisms (SNPs) (e.g., rs520692, rs3131296, and rs2071287) (Ikeda et al, 2013;Tochigi et al, 2007;Wang et al, 2006). Recently, study among 218 Taiwanese families has found another SNP, rs204993 with significant relationship with schizophrenia through testing the association of the entire genomic region of NOTCH4 (Liu et al, 2007). Specially, the AA genotype of rs204993 was associated with a higher risk for schizophrenia in the Chinese Han population (Zhang et al, 2015a).…”
Section: Introductionmentioning
confidence: 91%